Edukasi Modul Sumping (Support Suami Pendamping) Sebagai Persiapan Persalinan Bagi Ibu Dan Calon Pendamping Persalinan - Rullyni, Nurniati Tianastia; Dewi, Utami; Putri, Sabtini Ika (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2025)
The presence of the husband as a labor companion plays a crucial role as it can create a sense of safety and comfort, boost the mother's confidence, reduce anxiety about the childbirth process, lessen labor pain intensity, decrease childbirth complications, and speed up the labor process. Therefore, efforts to improve the knowledge and attitude of husbands in labor companionship through the